New Clinicopathologic Scenarios of EBV+ Inflammatory Follicular Dendritic Cell Sarcoma: Report of 9 Extrahepatosplenic Cases. (June 2021) - Jiang, Xiang-Nan; Zhang, Yan; Xue, Tian; Chen, Jie-Yu; Chan, Alex C.L.; Cheuk, Wah; Chan, John K.C.; Li, Xiao-Qiu
Abstract : EBV + inflammatory follicular dendritic cell (FDC) sarcoma is an indolent malignant neoplasm of spindled FDCs with a rich lymphoplasmacytic infiltrate and a consistent association with Epstein-Barr virus (EBV). It occurs exclusively in the liver and spleen, with the exception of a few colonic examples. In this study, we report 9 extrahepatosplenic cases, including 4 occurring in previously undescribed sites, but all apparently anatomically related to the aerodigestive tract. The cases included 5 gastrointestinal tumors all presenting as colonic pedunculated polyps, 2 presenting as mesocolon mass, and 2 involving the palatine or nasopharyngeal tonsils. One patient with a colonic tumor was complicated by paraneoplastic pemphigus. The patients had a median age of 58 years, with female predominance (female:male=7:2). A favorable outcome was observed in 7 patients. Histologically, EBV + inflammatory FDC sarcomas arising from these anatomic sites were similar to their hepatosplenic counterparts. Spindled to oval neoplastic cells with ill-defined cell borders were dispersed or formed loose whorled fascicles in a dense lymphoplasmacytic background. They had vesicular nuclei with distinct nucleoli and typically exhibited a range of nuclear atypia in the same case. The neoplastic cells showed variable expression of FDC markers and were labeled for Epstein-Barr virus–encoded RNA on in situ hybridization. These 9 cases thus broaden the clinicopathologic scenarios of EBV + inflammatory FDC sarcoma. Recognition of the potential existence of this tumor type in extrahepatosplenic sites permits a correct diagnosis to be made.